2020
DOI: 10.1097/adm.0000000000000704
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific Associations of Alcohol Withdrawal in Patients Admitted for the Treatment of Alcohol Use Disorder

Abstract: Objectives: There are sex differences in the pattern of alcohol consumption and in the complications of alcohol use disorder (AUD). We aimed to identify sex-specific differences in the factors associated with alcohol withdrawal syndrome (AWS) among patients that requested a first treatment for AUD. Methods: We enrolled 313 patients (75% men) with a Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition) AUD diagnosis that started treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Studies that incorporate item response theory models could shed light on the extent to which each withdrawal symptom contributes to the AWS diagnosis. Our finding of increased odds of AWS among males is consistent with conclusions from prior studies (Desmukh et al, 2003;Martin et al, 2018;Sanvisens et al, 2021;Schuckit et al, 2003). This contrasts with the conclusions of a review that neither age nor gender are significant correlates of alcohol withdrawal (Goodson et al, 2014), though the studies reviewed there focused on specific severe withdrawal symptoms (e.g., delirium tremens), rather than the withdrawal syndrome per se.…”
Section: Discussionsupporting
confidence: 88%
“…Studies that incorporate item response theory models could shed light on the extent to which each withdrawal symptom contributes to the AWS diagnosis. Our finding of increased odds of AWS among males is consistent with conclusions from prior studies (Desmukh et al, 2003;Martin et al, 2018;Sanvisens et al, 2021;Schuckit et al, 2003). This contrasts with the conclusions of a review that neither age nor gender are significant correlates of alcohol withdrawal (Goodson et al, 2014), though the studies reviewed there focused on specific severe withdrawal symptoms (e.g., delirium tremens), rather than the withdrawal syndrome per se.…”
Section: Discussionsupporting
confidence: 88%
“…Evaluation of the severity in each test revealed that 52% of the EtOH‐exposed mice had a high SS, and only 16% of the mice in the EtOH group had above‐median severity in all behavioral metrics. This is consistent with human population studies that have found that only a subset of individuals with an AUD exhibit AWS, with anxiety being among the most common symptoms of alcohol withdrawal (Caetano et al, 1998; Hall & Zador, 1997; Sanvisens et al, 2021). Therefore, preclinical investigators in the alcohol field are exhorted to take these percentages into consideration when determining sample sizes and designing experiments to examine EtOH withdrawal.…”
Section: Discussionsupporting
confidence: 84%
“…Gómez-Méndez et al ( 67 ) reported that among patients admitted with AWS, whether primary (as reason for admission) or secondary diagnosis of AWS, 88% (49,646/56,393) of them were males. Sanvisens et al ( 8 ) conducted a study with patients who had requested treatment for AUD and found that males [76.5% (179/234)] experience AWS more than females [64.6% (51/79), p = 0.038]. Salottolo et al ( 54 ) reported that among 28,101 patients [57.94% (16,140/28,101) males, 42.06% (11,715/28,101) females] admitted to trauma centers, patients who developed AWS were mostly males [205/246 (83.33%), p < 0.001].…”
Section: Resultsmentioning
confidence: 99%
“…Schuckit et al ( 39 ) compared 160 men and 51 women with severe AWS, the two groups were not significantly different in the age of onset of alcohol dependence (males vs. females: 24.5 ± 8.9 vs. 23.5 ± 8.8 years), years of heavy drinking (14.2 ± 10.0 vs. 11.0 ± 8.5), frequency of drinking (6.0 ± 1.8 vs. 5.4 ± 2.1 days per week), and total number of alcohol use problems (33.3 ± 6.2 vs. 32.5 ± 6.2). Family history of AUD was found to be a risk factor for AWS in women (OR = 2.85, 95% CI: 1.07–7.54) ( 8 ) while amount of alcohol consumption was a risk factor for AWS in both men and women, although it was more likely in women ( 75 ). Earlier onset of alcohol consumption (OR for every 5 years = 1.89, 95% CI:1.69–2.08) was associated with increased probability of AWS in men ( 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation